Effect of Water-Mixed Polyvinyl Alcohol Viscosity on Wear Response of Carbon Steel Exposed to an Eroding Medium - Naz, M.Y. (Springer, 2021)
The erosion failure of oil transmission lines is mainly caused by the migration of quartz, sand, silt and clay into the processing units. Apart from the solid particles, the fluid viscosity also impacts the erosion-related failure of the processing units. The role of sand carrier viscosity in wear damage to pipelines, however, is not well understood. In this study, the wear performance of carbon steel coupons in polymer-sand-water slurry was investigated by varying the slurry viscosity from 1 to 19 cP. The water-soluble polyvinyl alcohol was usedÂ to modify the viscosity of the carrier fluid. At a fluid velocity of 6 m/s, the Reynolds number decreased from 165,000 to 8684 with a rise in viscosity from 1 to 19 cP. Similarly, at 10 m/s, the Reynolds number decreased from 330,000 to 17,368 for a similar change in the fluid viscosity. Each coupon was exposed to the fluid stream for 10 hours. Universal scanning probe microscopy (USPM) revealed more rough topology at lower viscosities and relatively smoother topology at higher viscosities. The erosion rate decreased from 6.31 Â± 0.41 to 1.27 Â± 0.16 mm/year and microhardness from 102 VHN to 98.2 VHN with a rise in viscosity from 1 to 19 cP. The USPM method revealed slightly higher erosion rates as compared to the weight loss method. Â© 2021, ASM International.